Penerapan Metode Diskusi dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran PAI - Rosna, Rosna (LP3M STAI Ibnurusyd, 2023)
The learning method is an important factor in efforts to increase student motivation in the learning process at school. The purpose of this study was to analyze the successful application of the discussion method in increasing student motivation in Islamic religious education subjects at North Sangatta 2 Public Middle School. The method used in this research is a class action research method with Kurt Lewin's class action research model which consists of four steps, namely, Plan, do, observe, and Reflect. The result is that the use of the discussion method can increase student motivation in learning Islamic religious education. The increase in student learning motivation can be seen by: 1) Learning becomes more fun, 2) Students become more active in asking and responding to lessons in class, 3) Increasing student final results both in terms of knowledge and skill scores.